Penerapan Hukum Ketenagakerjaan Dalam Hubungan Industrial Untuk Mewujudkan Keadilan Pekerja Pada Karang Taruna Desa Pugeran, Kecamatan Gondang, Kabupaten Mojokerto - Dyan Arni Firmanti; Dewi Putri Anjani; Puri Rahayu; Dea Intan Putri; Intan Lailatul Husnah; Asta Lycha Shenandy; Achmad Rhodianto (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2023)
This community service aims to examine the application of labor law in industrial relations in order to realize worker justice in Karang Taruna Pugeran Village, Gondang District, Mojokerto Regency. Karang Taruna is a youth organization that focuses on empowering youth and improving community welfare. This research was conducted with the aim of understanding the level of understanding and implementation of labor law and identifying the obstacles that exist in achieving worker justice in the Karang Taruna environment. The application of labor law in industrial relations to achieve worker justice stems from the need for protection of workers' rights and the creation of a balanced relationship between workers and employers. In this context, labor law aims to regulate the rights and obligations of workers and employers in order to create a fair working relationship.